Blinded by the sunlight emerging from the prison of Saddam's Iraq - McAllester, Matthew (HarperCollins, 2004)
A Pulitzer Prize-winning journalist and Iraqi prison survivor shares the story of his incarceration and the obstacles that were overcome to secure his release, in a personal account that also gauges the prospects of Iraqis during and after Saddam Hussein's rule.
Keywords: McAllester, Matthew <1969->; Geschichte 2003; Geschichte; Gevangenisstraf; Golfoorlog (2003); Journalisten; Iraq War, 2003-; Journalists -- United States -- Biography; Gefängnis; Gefangener; Golfkrieg -- 2003; Amerikaner; Journalist; Irak; USA; Iraq -- History -- 1991-2003; Biografie; Erlebnisbericht